Mid-term effect of customized graduated elastic compression stockings for managing occupational edema: A randomized controlled trial - Wang, Sheng-Xing; Yang, Wen-Tao; Jin, Zhen-Yi; Wen, Jia-Hao; Ren, Hua-Liang; Xiong, Ying; Tao, Xiao-Ming; Li, Chun-Min (Vascular medicine (London, England), 2025)
This study compared the effectiveness of customized graduated elastic compression stockings (c-GECS) based on individual lower-leg parameter models with standard graduated elastic compression stockings (s-GECS) in patients with occupational edema (OE). A single-blind, randomized controlled trial was conducted with 70 patients with OE, randomly assigned to the c-GECS or s-GECS group. Follow-up assessments were performed at 1 and 3 months. Primary outcomes comprised visual analog scale scores (1-10) for lower-limb symptoms and comfort level of GECS. Secondary outcomes included GECS usage duration, calf volume, and interface pressure at B and C points (B: minimal ankle circumference point; C: maximum calf circumference point). Both groups exhibited significant improvements in pain, heaviness, and swelling symptoms at the 1- and 3-month follow up. At the 3-month follow up, the c-GECS group showed significantly superior improvement in symptoms. Comfort assessment revealed that c-GECS (16.2 ± 2.9) provided significantly greater comfort than s-GECS (13.6 ± 3.2) ( < 0.001). However, the two groups showed no significant difference in GECS wear duration. At 3 months, the c-GECS group showed superior maintenance of stocking tension at point B ( = 0.018). Both types of GECS significantly reduced calf volume at both time points, with no notable difference between the groups. c-GECS effectively alleviated pain, heaviness, and swelling symptoms in patients with OE. Although c-GECS did not exhibit a clear advantage in reducing calf volume as compared to s-GECS, it provided more stable and enduring pressure, enhanced the overall fit of GECS, and improved comfort during wear.